Impact of the COVID-19 pandemic on the outcomes of colorectal cancer surgical patients treated at a public hospital in Southern Brazil - Moszkowicz, Thiago Lucas Bastos de Melo; Gonçales, Tierre Aguiar; Debastiani, Mariana Severo; Herwig, Gabriela Klein; Manfroi, Laura Martin; Marolli, Carolina de Moura; Alves, Rafael José Vargas; Bica, Claudia Giuliano (Frontiers in Surgery, 2025)
PurposeThe pandemic has had a clear impact on surgical procedures, leading to a significant decline in volume due to the postponement of non-emergency operations. This has permitted healthcare providers to reallocate personnel and resources to address the ongoing coronavirus pandemic. The present study aims to assess the impact of the COVID-19 pandemic on mortality and the evolution of the clinical condition of colorectal tumors in surgical patients in a hospital unit of the Brazilian public health system.MethodsThis is a cohort study evaluating 263 adult patients with colorectal tumors who underwent surgery between January 2019 and March 2020 (pre-pandemic period) and between March 2020 and April 2021 (pandemic period) in the Unified Health System (SUS) in a tertiary hospital in southern Brazil. The first follow-up was carried out 30 days after surgery and the second at the end of the participants' hospitalization period. Primary Outcome(s) and Measure(s): The primary outcome was mortality up to 30 days after surgery. Secondary outcomes related to coronavirus infection included length of hospital stay, intensive care unit admission, overall mortality, emergency or palliative surgery, histopathological variables and advanced-stage tumors. Logistic regression was used to determine the potential relationship between the pandemic period and the outcomes of advanced cancer, emergency surgery, and 30-day mortality.ResultsThe study included 263 patients; 145 (55.1%) underwent surgery during the pandemic period and 118 (44.9%) in the pre-pandemic period. Coronavirus infection was associated with increased 30-day mortality, death, length of stay, and admission to the intensive care unit. Moreover, logistic regression confirmed that during the pandemic period, emergency surgeries increased but did not affect advanced cancer progression or 30-day mortality in cancer patients.ConclusionsThe pandemic period did not significantly influence overall mortality or 30-day mortality, nor did it affect the incidence of advanced cancer. These findings underscore the critical importance of maintaining surgical operations during pandemic periods.